PENGARUH PEMBELAJARAN DARING (ONLINE) TERHADAP KETERAMPILAN SOSIAL MAHASISWA UNIVERSITAS PENDIDIKAN INDONESIA - Ratih Lestari, - (2022)
This research is based on the influence of online learning that affects changes in student social skills during online learning. These changes are caused by several obstacles that can hinder the online learning process so that communication and interaction cannot run smoothly. The purpose of this study was to determine whether there was an effect of online learning on the social skills of students at the University of Indonesia Education. The research method used is descriptive quantitative with a survey approach. The sample in this study were active students of the Indonesian University of Education, namely students of the 2017 grade, 2018 and 2019 from 8 faculties. Data collection techniques by distributing online questionnaires via google forms, and interviews via the Whatsapp application. The data analysis technique used is hypothesis testing with t-test, f test, and coefficient of determination test. The results of the study indicate that there is an influence of online learning on social skills in interpersonal behavior and those related to group assignments of Indonesian University of Education students. The implication of this research for students is to use the results as motivation to develop social skills that the importance of social skills during online and offline learning as well as adaptation of new habits in the face of online learning to remain effective. And for other researchers, it can be a reference material for further research related to the Effect of Online Learning on the Social Skills of Indonesian University of Education Students.